Efeitos do distanciamento social causado pela Pandemia da Covid-19 na qualidade de vida e estado de depressão em idosos que participavam de um programa de exercícios físicos - AMORIM, Rosane Constância Madeira (2023)
Purpose: A verification the perception of quality of life, possible symptoms of depression in the elderly during social isolation caused by the COVID-19 pandemic. Materials and methods: The study included 19 elderly people who were divided into two groups: those who belonged to a regular physical exercise program GEF (n=8) and the group that did not participate in any regular physical exercise program GC (n=11), with mean ages of 70.2±6.9 and 70.3±6.3 years respectively. The variables of quality of life (SF-36) and possible symptoms of depression (GDS-30) collected in the pre-pandemic moment in 2019-2020 were investigated, as well as data relating to these aspects collected at the time of the pandemic in 2021, added to the scale of fear in relation to COVID-19. The collections of data occurred through telephone calls and online experiments using Google Forms or scheduled face-to-face meetings. Statistical analysis: To analyze the effects of social isolation on depression, a non-parametric analysis (qualitative data) and non-parametric analyzes of variance were used to compare the inter (non-paired measure - Mann-Whitney test) and intra (paired measure - Wilcoxon test) moments groups. The data referring to the COVID 19 fear scale were analyzed using the Mann-Whitney test and are presented as median and interquartile range (Q1 – Q3). For the analysis of the quality domains, ANOVA for 2 repeated measures was used to compare different moments and groups, with the results presented as mean ± standard deviation and we adopted a significance level of p<0.05. Results: Was found as a result as for fear of COVID-19, the GEF 22.5(19.5 27.5) group compared to GC 15 (14–19) expressed greater fear, representing a significant difference (p<0.05). In the results referring to the screening of depressive symptoms (GDS-30) in the intergroup comparisons of the GEF pre 5.5 (4.7–8) and pandemic 7 (4.5 – 8.2) and the GC pre 8 (4. 5 – 10) and pandemic 7 (5.5 – 9.5), there were no significant differences, but the GEF group had a higher score on the scale when compared to the pre pandemic group. Among the Quality-of-Life domains (SF 36), no significant difference was found in inter and intragroup comparisons. Conclusion: During the COVID-19 pandemic period, no differences were observed in quality of life and symptoms of depression in groups of elderly people who participated in a physical activity project and elderly people who did not participate in any exercise group. The low adherence to social distancing and the adoption of spontaneous physical activity carried out by both groups probably influenced the results found in the present study.